EFEKTIVITAS PASAL 105 UNDANG-UNDANG NOMOR 6 TAHUN 2011 JO PASAL 249 PERATURAN PEMERINTAH NOMOR 31 TAHUN 2013 DALAM HUBUNGAN DENGAN KEGIATAN WNA (Studi Kasus di Kota Pontianak) - NIM. A1012211137, ALIF NUR QOMARUDDIEN (Jurnal Fatwa Hukum, 2025)
Abstrac  Provisions in the Criminal Code regulate that every investigation carried out by PPNS must be under the coordination of a National Police investigator, as with the authority of PPNS investigators regulated in Law no. 6 of 2011 concerning Immigration. To anticipate that there will be no overlap in authority between PPNS investigators and Polri investigators, it is necessary to have a relationship or coordination between immigration PPNS investigators and Polri investigators in conducting investigations as regulated in Article 107 paragraph (1) of the Immigration Law. This research aims to determine the coordination between PPNS Immigration investigators and Polri investigators in carrying out investigations of immigration crimes in the Pontianak Class I Immigration jurisdiction, with the aim of knowing the implementation of coordination between PPNS Immigration and Polri investigators in investigating immigration crimes and knowing the obstacles between PPNS Immigration and Investigators. The National Police in coordinating investigations of immigration crimes.This research is descriptive analytical in nature, which leads to empirical juridical research. The type of data used in this research comes from primary and secondary sources. Primary data was obtained from the results of field research, while secondary data was obtained from the results of library research consisting of primary, secondary and tertiary legal materials. Data analysis used in research is descriptive data analysis. Based on the results of research and discussion, since the publication of Law no. 6 of 2011 concerning Immigration, the investigation of violations of immigration law is a special authority given by law to immigration civil servant investigators.The implementation of coordination between Immigration PPNS has not been carried out in accordance with the provisions of the law. The obstacles for the Immigration PPNS in coordinating investigations of immigration crimes are due to the limitations of the immigration PPNS, starting from the lack of Human Resources (HR), both in terms of quantity and quality. Meanwhile, the obstacles to Polri investigators in coordinating investigations into immigration crimes are: the weakness of Polri's authority in carrying out supervision and legal action. There is a lack of coordination between Immigration PPNS and National Police investigators, due to institutional egoism and a narrow understanding of coordination among Immigration PPNS.Keywords: coordination, violations, immigration crimes. LIST OF CONTENTS  Abstrak  Ketentuan dalam KUHP mengatur dimana setiap penyidikan yang dilakukan oleh PPNS harus berada di bawah koordinasi dari penyidik Polri, sebagaimana dengan kewenangan penyidik PPNS diatur dalam Undang-Undang No. 6 Tahun 2011 Tentang Keimigrasian. Mengantisipasi tidak terjadinya tumpang tindih kewenangan antar penyidik PPNS dengan Penyidik Polri diperlukan adanya hubungan atau koordinasi antara penyidikan   PPNS keimigrasian dengan penyidik Polri dalam melakukan penyidikan sebagaimana diatur dalam Pasal 107 ayat (1) Undang-Undang Keimigrasian. Penelitian ini bertujuan untuk mengetahui koordinasi penyidik PPNS Keimigrasian dan penyidik Polri dalam melakukan penyidikan terhadap tindak pidana Keimigrasian diwilayah hukum Keimigrasian Kelas I pontianak, dengan tujuan untuk mengetahui pelaksanaan koordinasi antara PPNS Keimigrasian dengan penyidik Polri dalam penyidikan tindak pidana Keimigrasian dan mengetahui hambatan PPNS Keimigrasian dan Penyidik Polri dalam melakukan koordinasi terhadap penyidikan tindak pidana keimigrasian.Penelitian ini bersifat deskriptif analitis, yang mengarah kepada yuridis empiris. Jenis data yang digunakan dalam penelitian ini adalah bersumber dari primer dan sekunder. Data primer diperoleh dari hasil penelitian lapangan, sedangkan dari sekunder diperoleh dari hasil penelitian kepustakaan yang terdiri dari bahan hukum primer, sekunder dan tersier. Analisis data yang digunakan dalam penelitian, yaitu analisis data deskriftif analisis. Berdasarkan hasil penelitian dan pembahasan, sejak diterbitkannya Undang-Undang No. 6 Tahun 2011 Tentang Keimigrasian, maka penyidikan terhadap pelanggaran hukum keimigrasian menjadi kewenangan khusus yang diberikan undang-undang kepada penyidik PNS keimigrasian.Pelaksanaan koordinasi antara PPNS Keimigrasian belum berjalan sesuai dengan ketentuan undang-undang. Hambatan PPNS Keimigrasian dalam melakukan koordiasi penyidikan tindak pidana keimigrasian, yaitu karena keterbatasan yang dimiliki oleh PPNS keimigrasian, mulai dari masih kurangnya Sumber Daya Manusia (SDM), baik dilihat dari kuantitas maupun kualitasnya. Sedangkan hambatan penyidik Polri dalam melakukan koordinasi penyidikan tindak pidana keimigrasian, yaitu: lemahnya kewenangan Polri dalam melakukan pengawasan dan penindakan hukum. Kurangnya koordinasi antara PPNS Keimigrasian dengan penyidik Polri, karena egoisme kelembagaan dan pemahaman yang sempit tentang koordinasi pada PPNS Keimigrasian.Kata Kunci : koordinasi, Pelanggaran, Tindak Pidana Keimigrasian.